From Centralized To Decentralized Service: Mental Health And Psychiatry In Malaysia - Por, Heong Hong (Springer Nature, 2017)
This chapter charts the fonnation and transfonnation of mental institu- 1,ons, therapeutic concepts, and psychiatric practices in Malay(si)a from the early 11ineteenth century throughout the post-independence era. Introduced by colonial- 1'1S in the early nineteenth century, mental health institutions in Malaya started out ,I\ a colonial program that aimed to clean the colony of vagrants, starving migrants, paupers, drug addicts, convicts, and people afflicted with mental iUnesses by con- 1 ining them in gaols. It was not until the mid-nineteenth century that the mental .,sylum was separated from the gaol. At the tum of the twentieth century, an mcrease in the number of mentally ill patients coincided with the large influx of migrant workers from China and India. The overrepresentation of male Chinese patients mirrored the demographic structure of the immigrant population. Rncialized medical comprehension of mental illness was not uncommon. !'herapeutic practices included occupational therapy, shower baths or cold douches, and electroconvulsive treatment (ECT). These practices were an essential part of a hroader process of molding the mentally ill into economically productive, morally useful and desirable colonial subjects. As a set of transplanted practices, colonial institutional mental health services did not automatically acquire legitimacy. The availability of traditional healing services, the public preference for traditional therapies, and social stigma and scarce modem psychiatric services jointly contributed to the unpopularity of these mental health institutions. Several changes and debates took place after independence. The government took the initiative to decentralize mental health services by setting up psychiatric units at district and general hospitals from 1958. Local medical education began to offer psychiatric training to overcome the shortage of professionals.